جودة الحياة و علاقتها بالإنتماء الوطني لدی طلبة الجامعة دراسة میدانیة فی جامعة السلیمانیة - سالح, أ .م.د . میران محمد; حسین, د. شوخان محمود; محمد, د. شیرین ابراهیم (Sulaimani Journal for Humanities, 2023)
The quality of life and its relationship to national belonging to the university students A field study at the University of Sulaymaniya The aim of this research is to determine the level of quality of life and national belonging, the differences in statistical indicators of the university students towards the quality of life and national belonging according to these variables (gender, age, social background, and students' discipline). Also the (relations between quality of life and national belonging among the university students). This research consists of three parts, the first part involves the general framework of the research, definition of the concepts and the presentation of previous researches, the second part consists of the theoretical framework of quality of life and national belonging. The third part includes the research methods and field phases, and the research use the (descriptive, social survey, comparative) methods to achieve its objectives. The research community is the students of Sulaimani University. A sample of 180 people was randomly selected. The most important tools used in the research are two measures (quality of life), (national belonging) measurements. Moreover, in the third part of the research, the results of the research are presented. As the most important results are:- 1. A low quality of life and national belonging in the study sample. 2. Lack of statistical differences in quality of life and the national belonging according to the variables (gender, age, social background, and students' discipline). 3. There is a direct positive relationship between quality of life and national belonging. Finally, in the light of the research, a number of recommendations and suggestions have been addressed to the Stakeholders and researchers